Differential mechanisms of posterior cingulate cortex downregulation and symptom decreases in posttraumatic stress disorder and healthy individuals using real‐time fMRI neurofeedback. Issue 1 (18th December 2021) - Nicholson, Andrew A.; Rabellino, Daniela; Densmore, Maria; Frewen, Paul A.; Steryl, David; Scharnowski, Frank; Théberge, Jean; Neufeld, Richard W.J.; Schmahl, Christian; Jetly, Rakesh; Lanius, Ruth A.
Abstract: Background: Intrinsic connectivity networks, including the default mode network (DMN), are frequently disrupted in individuals with posttraumatic stress disorder (PTSD). The posterior cingulate cortex (PCC) is the main hub of the posterior DMN, where the therapeutic regulation of this region with real‐time fMRI neurofeedback (NFB) has yet to be explored. Methods: We investigated PCC downregulation while processing trauma/stressful words over 3 NFB training runs and a transfer run without NFB (total n  = 29, PTSD n  = 14, healthy controls n  = 15). We also examined the predictive accuracy of machine learning models in classifying PTSD versus healthy controls during NFB training. Results: Both the PTSD and healthy control groups demonstrated reduced reliving symptoms in response to trauma/stressful stimuli, where the PTSD group additionally showed reduced symptoms of distress. We found that both groups were able to downregulate the PCC with similar success over NFB training and in the transfer run, although downregulation was associated with unique within‐group decreases in activation within the bilateral dmPFC, bilateral postcentral gyrus, right amygdala/hippocampus, cingulate cortex, and bilateral temporal pole/gyri. By contrast, downregulation was associated with increased activation in the right dlPFC among healthy controls as compared to PTSD. During PCC downregulation, right dlPFC activation was negatively correlated to PTSD symptom severity scores and difficulties in emotion regulation. Finally, machine learning algorithms were able to classify PTSD versus healthy participants based on brain activation during NFB training with 80% accuracy. Conclusions: This is the first study to investigate PCC downregulation with real‐time fMRI NFB in both PTSD and healthy controls. Our results reveal acute decreases in symptoms over training and provide converging evidence for EEG‐NFB targeting brain networks linked to the PCC. Abstract : This is the first study to investigate PCC downregulation with real‐time fMRI NFB in both PTSD and healthy controls. Our results reveal acute decreases in symptoms over training and provide converging evidence for EEG‐NFB targeting brain networks linked to the PCC.